Eco‐driving strategies in battery electric vehicle use – how do drivers adapt over time?. Issue 7 (1st September 2015) - Neumann, Isabel; Franke, Thomas; Cocron, Peter; Bühler, Franziska; Krems, Josef F.
Abstract : Eco‐driving is of high importance when driving battery electric vehicles (BEVs) in terms of prolonging the vehicle's limited range. A longitudinal field study with 40 participants was conducted to examine which eco‐driving strategies users know before and after driving a BEV for 3 months. Furthermore, participant's knowledge regarding eco‐driving strategies with BEVs against internal combustion engine vehicles (ICEVs) was compared. After 3 months of BEV usage, a driving test was applied in order to investigate the strategies drivers apply to drive energy efficiently and to estimate the effectiveness of these strategies. Results reveal that reported eco‐driving strategies for BEVs and ICEVs differ significantly. Users reported significantly more BEV eco‐driving strategies after experiencing the BEV for 3 months than before. Furthermore, drivers were able to significantly reduce energy consumption by applying eco‐driving strategies in the driving test. Reported eco‐driving strategies proved to be effective. The results imply that eco‐driving strategies for ICEVs have to be adapted for BEV eco‐driving and that drivers gain a deeper understanding of factors that influence energy consumption by experiencing the BEV for a longer period of time. Based on the results, support of the driver through training or assistance systems is recommended.